Farm Family Exposure to Glyphosate - Frederick M. Fishel (EDIS)
PI-178, an 8-page fact sheet by Frederick M. Fishel, summarizes the results of the Farm Family Exposure Study, conducted in 2000 to determine farm-family exposure to the commonly applied herbicide, glyphosate. Includes additional sources of information. Published by the UF Department of Agronomy, May 2009.